Analisis Pemilihan Moda Transportasi antara Kereta Api dan Bus Rute Makassar - Parepare Ditinjau dari Efektifitas dan Efisiensi - Merlyn, Ambarita Rusmiar; Nurdin, Abdul Rahim; Yunianti, Nurhadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Transportation development by the government is increasingly intensive to be carried out in accordance with public interest, which many choose to travel using public transportation. People then demand to use the most efficient mode of transportation to support travel in today's modern era, through several considerations including economic, social and environmental aspects. Until now, people, especially the city of Makassar, still choose to travel between regions and cities using train and bus transportation. This research will be conducted on the Train and Bus route Makassar- Parepare bus services that will be discussed in this study are buses that start traveling from Makassar Regional Terminal Daya with the aim of Parepare. This research aims to analyze the selection of transportation modes between trains and buses on the Makassar-Parepare route in terms of effectiveness and efficiency. The method used in this research is quantitative method in the form of questionnaire survey and descriptive statistical analysis in collecting data results. The results obtained show that public interest in the two means of transportation is concluded that train transportation is more desirable in terms of effectiveness and efficiency.